2016
DOI: 10.1111/pan.13050
|View full text |Cite|
|
Sign up to set email alerts
|

Current evidence for the use of sugammadex in children

Abstract: Sugammadex is a novel pharmacologic agent, which reverses neuromuscular blockade with a mechanism that differs from the commonly used, acetylcholinesterase inhibitors. Although sugammadex has not received approval from the United States Food & Drug administration in children, its use has already been reported to reverse neuromuscular blockade in several clinical scenarios in the pediatric population including the 'cannot intubate-cannot ventilate' scenario. To date, there remains limited data from prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…There are few clinical trials reported in the English language of the use of sugammadex in children, which have been reviewed recently by Tobias. 58 Only a dose of 2 mg kg À1 to reverse moderate neuromuscular block is recommended on the sugammadex data sheet for use in paediatric practice in the UK, and the drug does not yet have approval in this country for use in neonates.…”
Section: Reversal Of Neuromuscular Blockmentioning
confidence: 99%
“…There are few clinical trials reported in the English language of the use of sugammadex in children, which have been reviewed recently by Tobias. 58 Only a dose of 2 mg kg À1 to reverse moderate neuromuscular block is recommended on the sugammadex data sheet for use in paediatric practice in the UK, and the drug does not yet have approval in this country for use in neonates.…”
Section: Reversal Of Neuromuscular Blockmentioning
confidence: 99%
“…Other effects of sugammadex on cardiac conduction include a potential to prolong the QTc interval. 15 In a prospective evaluation of the efficacy of sugammadex in reversing neuromuscular blockade, 176 adult patients anesthetized with propofol were randomly assigned to receive sugammadex (2,4,8,12, or 16 mg/kg) or placebo at 3 or 15 minutes after rocuronium (1 or 1.2 mg/kg) during propofol anesthesia. Although there was prolongation of the QTc interval in 9 patients, this was considered to be related to sugammadex in only 1 patient.…”
Section: Discussionmentioning
confidence: 99%
“…1 Sugammadex (Bridion, Merck & Co, Whitehouse Station, NJ) is a novel pharmacologic agent with a unique mechanism of action for the reversal of neuromuscular blockade. 2 The reader is referred to Tobias 2 for a review of its use in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…However, sugammadex can now be used for rapid restoration of normal neuromuscular function. 45 The importance of considering laryngospasm and effectively treating it have recently been emphasized by an editorial written by Drs. Weiss and Engelhardt.…”
Section: Tablementioning
confidence: 99%